The Genus Chenopodium: Phytochemistry, Ethnopharmacology and Pharmacology - Kokanova-Nedialkova, Zlatina; T. Nedialkov, Paraskev; D. Nikolov, Stefan (Pharmacognosy Reviews)
The review includes 154 references on the genus Chenopodium covered up to December 2008 and has been compiled using references mainly from Chemical Abstracts and Pubmed. This article briefly reviews the phytochemistry, ethnopharmacology and pharmacology of Chenopodium genus. Three hundred seventy nine compounds isolated from different species are reported. Fenolics, flavonoids, saponins, ecdysteroids and triterpenoids were the major classes of phytoconstituents of this genus. The detailed distribution of these compounds among the different Chenopodium species with the related references is given in tables. In addition, this review discusses the traditional medicinal uses of different Chenopodium species as well as recent developments done in this aspect.
Keywords: Chenopodium; chemical constituents; folk medicine; pharmacology